(untitled) (Research, Society and Development, 2022)
With the increasing urban expansion and the increase in the number of condominiums, a more economical and sustainable alternative supply are the artesian wells that can provide safe water for consumption. However, this water is also subject to contamination by pathogens and may undergo physical and chemical changes. The objective of this study was to analyze the water portability characteristics of artesian wells in condominiums in the city of Vitória da Conquista - Ba. This is a descriptive research of exploratory experimental nature, with quantitative approach. The collection of water samples from artesian wells was concentrated in five condominiums, chosen randomly. Physical and chemical parameters such as pH, turbidity, conductivity, temperature, total alkalinity and aluminum were analyzed. In the microbiological samples, contamination by total and thermotolerant coliforms and parasitological analyses were evaluated. It was verified that the water of all wells does not meet the standards of portability established by Legislation 888/2021, which suggests the need for a better control of these wells artesian.